POTENSI DAYA TARIK DESA WISATA RANTAU BAIS KABUPATEN ROKAN HILIR PROVINSI RIAU - Harmigi, Amin; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Tourism potential is all that is owned by a tourist attraction that is useful for developing the tourism industry in certain areas. Attraction can attract tourists to visit must meet the requirements of development that is (1) What to see, (2) What to do, (3) What to buy, (4) What to arrived, (5) What to stay. This research aims to (1) to know the potential of tourist attraction Rantau Bais Rokan Hilir regency of Riau Province, and (2) To know the response of stakeholders about the potential of tourist attraction Rantau Bais Rokan Hilir regency of Riau Province. This research uses qualitative method with descriptive approach, research subject is rantau bais village head, Pokdarwis chairman, community and public figure and tourism office of youth and sport. Data collection is done by observation, interview and documentation. Data analysis used in this research is data reduction data, data presentation, and conclusion. The results of this study indicate that Rantau Bais tourism village has the potential of natural tourism attraction, the potential of cultural tourism attraction and the potential of special interest tourism attraction. The potential of natural attraction of flora and fauna, tilan island and river rokan. The potential of cultural tourism attractions are customs such as customs of marriage and sunnah rasul, home of typical Malay carving, oldest mosque, long grave and suluk. Potential attractions are special interest attractions, adventure around the island and fishing. The conclusion of this research is to maximize the potential of tourist attraction in Rantau Bais village, by adding tourist attraction to attract tourists coming to the village, as well as repairing and equipping infrastructure facilities by cooperating with the government. Keywords : Tourism Potential, tourist attraction, Tourism Village